2021
DOI: 10.1002/chem.202100007
|View full text |Cite
|
Sign up to set email alerts
|

Overview of N‐Rich Antennae Investigated in Lanthanide‐Based Temperature Sensing

Abstract: The market shareo fn oncontact temperature sensors is expending due to fast technological and medical evolutions. In the wide varietyo fn oncontact sensors, lanthanide-based temperature sensors stand out. They benefit from high photostability,r elativelyl ong decay times and high quantum yields. To circumvent their low molar light absorption, the incorporationo falight-harvesting antenna is required. This Review provides an overview of the nitrogenrich antennae in lanthanide-based temperature sensors, emitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 96 publications
(105 reference statements)
0
14
0
Order By: Relevance
“…In short, MOF has an outstanding network to perform facile rational engineering for fine-tuning of the light-emitting center to adjust the luminescent properties, and in addition, the stability of MOF that varies with temperature highlights them as a potential candidate for a luminescence temperature sensor. Lanthanide metal ions have a great role in a luminescence thermometer, and a careful literature survey revealed that the luminescent thermometer property is generally shown by the lanthanide-based MOF. The highly conjugated organic linkers can tune their various triplet energy states which helps to sensitize diverse lanthanide metal ions in the luminescent MOF by virtue of the various degrees of charge transfer that take place between ligand and lanthanide metal ion. Thus, the practical utility of MOF as a ratiometric luminescent thermometer with high sensitivity, quick response time, and tunable response range becomes possible.…”
Section: Ratiometric Sensing Application Of Mofmentioning
confidence: 99%
See 1 more Smart Citation
“…In short, MOF has an outstanding network to perform facile rational engineering for fine-tuning of the light-emitting center to adjust the luminescent properties, and in addition, the stability of MOF that varies with temperature highlights them as a potential candidate for a luminescence temperature sensor. Lanthanide metal ions have a great role in a luminescence thermometer, and a careful literature survey revealed that the luminescent thermometer property is generally shown by the lanthanide-based MOF. The highly conjugated organic linkers can tune their various triplet energy states which helps to sensitize diverse lanthanide metal ions in the luminescent MOF by virtue of the various degrees of charge transfer that take place between ligand and lanthanide metal ion. Thus, the practical utility of MOF as a ratiometric luminescent thermometer with high sensitivity, quick response time, and tunable response range becomes possible.…”
Section: Ratiometric Sensing Application Of Mofmentioning
confidence: 99%
“…Fluorescence sensors have been evolving swiftly since the first report of the emission spectra of a highly fluorescence dye molecule in 1905 by E. L. Nichols . Afterward, various fluorescent materials have been developed for the recognition of numerous analytes with diverse detection techniques ranging from single emission to multi-emission. , Recently, porous crystalline metal–organic frameworks (MOFs) constructed from metal ions/metal nodes and organic ligands , have drawn great attention as potential applications in the field of sensing, gas storage/separation and its sequestration, catalysis, , drug delivery, magnetism, and so forth . In the case of sensing, for well-designed MOFs, both the metal ions and the organic linkers can be emissive if they are judiciously selected.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the electronic, optical, and magnetic properties, organic (bio)­polymers are limited by their closed-shell atomic constituents. The introduction of open-shell d-block or f-block elements provides metallopolymers or hybrid materials, which can be exploited for promising applications in light-emitting diodes, in solid cells for photovoltaics, in magnetically active and light-emissive layers, in telecommunication devices, and in temperature sensors . Among the possible arrangements of the metal complexes with respect to the polymer backbone, referred to as Wolf types I–III (Scheme a), , only the type III polymers, in which a stochiometric amount of metals is part of the polymeric backbone, have been intensively investigated in inorganic chemisty.…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide-doped phosphors have attracted much attention from researchers in recent years due to the unique electronic structure of lanthanides. [1] To date, lanthanide-doped phosphors have been widely applied to lighting [2], display [3], biological imaging [4], temperature sensing [5], information storage, [6] fingerprinting, [7] anti-counterfeiting, [8] and other fields because of the characteristics of excellent photostability, narrow emission peaks, long lifetimes, large Stokes shifts and minimized photobleaching. It is well known that Tb 3+ ion is regarded as a promising green-emitting activator and Eu 3+ ion is regarded as a promising red-emitting activator.…”
Section: Introductionmentioning
confidence: 99%